Development of E-Worksheets Discovery Learning Model Assisted by Augmented Reality for Renewable Energy Topic - Alpi Fajarno; Yuberti; Ratu Dwi Gustia Rasyidi; Sri Latifah; Ajo Dian Yusandika (Jurnal Penelitian Pembelajaran Fisika, 2025)
The poor motivation and interest of students in learning physics which is frequently viewed as challenging and less interesting led to the conduct of this study. As a result, creating cutting-edge educational materials that may facilitate interactive learning and foster a deeper conceptual grasp is essential. Building an Electronic Student Worksheet on the subject of renewable energy using the Discovery Learning methodology enhanced by Augmented Reality is the aim of this study. The research and development (R&D) method for this study was conducted Subject matter and media experts validated the generated product, and teachers and high school students participated in restricted trials to verify its viability and usefulness. The findings show that professionals rated the Worksheet as highly valid, and both teachers and students found it to be very interesting and user-friendly. Therefore, it is possible to implement the Augmented Reality assisted Discovery Learning-based Worksheet in physics education, and it has the potential to improve students' engagement and comprehension of renewable energy ideas.